Seasonal Variations in Iceberg Freshwater Flux in Sermilik Fjord, Southeast Greenland From Sentinel‐2 Imagery. Issue 15 (10th August 2019) - Moyer, A. N.; Sutherland, D. A.; Nienow, P. W.; Sole, A. J.
Abstract: Iceberg discharge is estimated to account for up to 50% of the freshwater flux delivered to glacial fjords. The amount, timing, and location of iceberg melting impacts fjord‐water circulation and heat budget, with implications for glacier dynamics, nutrient cycling, and fjord productivity. We use Sentinel‐2 imagery to examine seasonal variations in freshwater flux from open‐water icebergs in Sermilik Fjord, Greenland during summer and fall of 2017–2018. Using iceberg velocities derived from visual‐tracking and changes in total iceberg volume with distance down‐fjord from Helheim Glacier, we estimate maximum average two‐month full‐fjord iceberg‐derived freshwater fluxes of ~1, 060 ± 615, 1, 270 ± 735, 1, 200 ± 700, 3, 410 ± 1, 975, and 1, 150 ± 670 m 3 /s for May–June, June–July, July–August, August–September, and September–November, respectively. Fluxes decrease with distance down‐fjord, and on average, 86–91% of iceberg volume is lost before reaching the fjord mouth. This method provides a simple, invaluable tool for monitoring seasonal and interannual iceberg freshwater fluxes across a range of Greenlandic fjords. Plain Language Summary: Recent studies have shown that the freshwater produced via the melting of icebergs can dominate the freshwater budget in glacial fjords surrounding the Greenland Ice Sheet, which has important implications for fjord circulation and heat budget, nutrient availability, and primary productivity. Here we use satellite imagery to estimate both iceberg velocity and the seasonal changes in iceberg volume in Sermilik Fjord in southeast Greenland in 2017–2018, from which meltwater fluxes are derived. Iceberg meltwater fluxes are highest in the late summer and fall, when fjord water temperatures are warmer than in the spring and early summer, and when more icebergs have been calved into the fjord. Throughout the year, the volume of freshwater generated from the melting of icebergs is greater than the freshwater entering the fjord at the base of the glacier and sourced from melting at the ice sheet surface. As such, the melting of icebergs provides a significant volume of freshwater to the fjord system, with important implications for fjord‐scale circulation and heat budget, nutrient cycling, and primary productivity. The methodology presented here is effective, simple and inexpensive, and can be applied to a variety of glacial fjord systems, particularly those that are remote and inaccessible. Key Points: Freshwater fluxes from iceberg melt in Sermilik Fjord have a seasonal signal, peaking across August and September in 2017 and 2018 Fluxes decrease with distance down‐fjord from Helheim Glacier, with ~86– 91% of iceberg volume lost before reaching the fjord mouth We present a simple and effective tool for monitoring iceberg freshwater fluxes across a range of Greenlandic fjords